What forms university? An integrated model from Syria - Mahmoud, Ali; Khalifa, Bayan (Business: Theory and Practice, 2015)
This study aims at developing and empirically testing an integrated model incorporating the factors that form university image in Syria. The study used a quantitative survey of students at Syrian universities. A pre-test of the questionnaire was undertaken using a convenient sample of 40 students. Thereafter, a sample of 259 students was used to test the model using structural equation modeling. The findings suggest word of mouth and faculty-individualized attention, one of service quality dimensions, as the antecedents of university image. Moreover, the findings reveal a positive effect of faculty-individualized attention and support staff helpfulness, as service quality dimensions, on student satisfaction. It is also found that student satisfaction positively affect word of mouth. This study is expected to help Syrian universities understand the key factors contributing to university image formation, and, therefore, strengthen their positions in the market. This study comes to be one of the first studies that attempt to understand how university image is formed.